Facile microwave synthesis of Zinc Ferrite@NCDs for photocatalytic degradation of fluoroquinolone antibiotics - Kaushal, Neha; Sarraf, Sonu; Basu, Aviru Kumar; Mishra, Sunita; Saha, Avishek (Materials Chemistry and Physics, 2024)
Zinc ferrite (ZnFe2O4) composites have attracted growing interest in photocatalytic water purification. Herein, the hybrids of zinc ferrite and nitrogen-doped carbon dots (ZnF@x%NCDs) were synthesized via facile micro-wave synthesis. X-ray diffraction and Raman characterization confirm the formation of the spinel structure, and elemental composition has been analyzed by X-ray photoelectron spectroscopy. The photocatalytic activity of ZnF@x%NCDs was evaluated via the decomposition of ciprofloxacin and norfloxacin under visible light illumination. We noted that 20 % weight loading of NCDs led to the highest (similar to 79.2 %) ciprofloxacin (CIP) degradation. Diffuse reflectance measurements demonstrate the reduction of the band gap in composites ZnF@20%NCDs (1.91 eV) compared with bare ZnF (2.03 eV); moreover, the hybridization of zinc ferrites with NCDs results in enhanced photocurrent density and surface area. The effect of experimental parameters, including the role of photocatalyst dosage, pH value, and initial concentration of pollutants on the degradation of CIP, have also been investigated.
Keywords: Carbon dots; Ciprofloxacin degradation; Norfloxacin degradation; Photocatalysis; Zinc Ferrite

Novel GO hoisted SnO2-BiOBr bifunctional catalyst for the remediation of organic dyes under illumination by visible light and electrocatalytic water splitting - Dhillon, Manshu; Naskar, Abhishek; Kaushal, Neha; Bhansali, Shekhar; Saha, Avishek; Basu, Aviru Kumar (NANOSCALE, 2024)
Keywords: Chemistry; Multidisciplinary; Nanoscience & Nanotechnology

Visible light-assisted ferro-photocatalytic application of bismuth ferrite nanoparticles synthesized at low temperature - Sarraf, Sonu; Kaushal, Neha; Chugh, Vibhas; Sundar, Adhiraj; Saha, Avishek; Basu, Aviru K. (Journal of Materials Science, 2024)
Polycrystalline nano-sized multiferroic bismuth ferrite was prepared by facile sole-gel method using acetic acid as a chelating agent followed by calcination at 450, 500, and 600 degrees C. Transmission electron spectroscopy and X-ray diffraction patterns revealed the crystallinity in the samples, and the crystallite size increased with calcination temperature. The calcination temperature also greatly influenced the grain size of the materials, and high calcination temperature induces a decline in the total surface area per unit mass of material. The ferroelectric polarization measurement showed a decrease in remnant polarization from 0.18 to 0.09 mu C/cm2 with an increase in temperature. The remnant polarization induced delayed recombination of charge carriers upon light illumination, and the high surface area led to the highest photocatalytic activity in 450 degrees C calcined samples. The higher photocurrent density in low-temperature calcined samples supports the visible-light photodegradation studies of Congo Red (CR) dye. A maximum of 76.6% photocatalytic activity was observed in the 450 celcius calcined bismuth ferrite samples. In summary, the higher photocatalytic efficiency in the low-temperature samples is attributable to the synergistic effect of relatively higher remnant polarization and higher surface area.